Validity and reliability test of an Electric Knee Height Measuring Device (EKHMD) predicting body height and nutritional status - Rajab, Alfian Abdul; Utami, Fista (Poltekkes Kemenkes Bandung, 2026)
Background: Direct height measurement is often difficult in immobilized patients. Knee height measurement becomes an alternative, thus encouraging the development of an electronic knee height measuring device (EKHMD). Objective: The aim of this study was to determine the validity and reliability of the EKHMD in estimating knee height, height, and nutritional status. Methods: This study used a quantitative approach with 30 healthy adults (15 men, 15 women) through purposive sampling. Anthropometric measurements used the EKHMD and a microtoise as standards. Validity was assessed using Pearson or Spearman correlation tests, agreement or accuracy using Bland–Altman plot analysis, and reliability using Cronbach-Alpha. Results: The results of the validity test showed that knee height measurements (r = 0.929), estimated height (r = 0.863 (sitting), r = 0.869 (lying down), and nutritional status (r = 0.952 (sitting), r = 0.970 (lying down) with significance for all variables (p = 0.00) which means that EKHMD correlated strongly with microtoise measurements (p < 0.05). Accuracy analysis using Bland–Altman measurements was in the range of Upper LoA and Lower LoA knee height (2.13 – (-1.43 cm)), estimated height (7.89 – (-9.05) cm (sitting) 0.049 (-0.029) cm (lying down)), and nutritional status (2.35 – (-2.01) (sitting), 0.06 – (-0.023) (lying down)) and Cronbach’s Alpha showed high reliability (p > 0.60), knee height (p=0.61), estimated height ((p=0.936 (Sitting), p=0.928 (Lying)), and nutritional status (p=0.983 (Sitting), p=0.984 (Lying)). Conclusion: Thus, EKHMD can be considered as a tool to measure estimated height and nutritional status but still needs to be developed further.